MINAT GURU MENJADI KEPALA SEKOLAH DI KABUPATEN KUDUS - Fatah Hidayat; Nurkolis Nurkolis; Rasiman Rasiman (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2016)
The purpose of this study is to describe and explain: (1) the teacher’s interest become principals in Kudus, (2 recruitment system of principals in Kudus; (3) the factors that cause interest and disinterest of teachers to become principals in Kudus; (4) the problems in the recruitment of principal at Kudus, and (5) the best solution in order to have an interest in becoming the principal at Kudus. This research was conducted in the UPT Pendidikan Kaliwungu Kudus with the respondent principals, teachers, and Kasie PTK Dikpora Kudus. The type and the approach that is used in this study is a qualitative descriptive approach. Data collection methods which is used is interviews and documentation. The analysis of the data used is descriptive analysis.The results of this study indicate that: (1) the majority of primary school teachers in the Kaliwungu Kudus don’t have interest in becoming principals because teachers feel comfortable and satisfied with his position as a teacher. Next, it is because of the burden and the task of the school head is heavier. Salaries and benefits received by teachers is more than enough also be because teachers do not intend to participate in the selection of the school head; (2) principal recruitment system in Kaliwungu Kudus covers the administration and academic selection. The recruitment model that is used is external recruitment. The recruitment procedures begin with data collection and mapping the number of principal empty formations. Then the official quotas applicants and make a selection announcement through a circular letter to all educational units. Applicants are asked to collect file administrative requirements. For those who pass the selection and administration will follow an academic test followed by interview and presentation.; (3) there are no factors that cause the interest of teachers to become principals. While the factors that cause the teachers are not interested in being the principal is the workload is too high when compared with teachers, compensation that is not balanced with the workload and physical readiness, mental and financial; (4) the obstacles in the recruitment principal at Kaliwungu Kudus covers compensation benefits to the principal are not balanced and the requirements of physical readiness, mental and materail; and (5) the best solution so that teachers have an interest in becoming the head of the school is to implement personnel management, especially in the provision of compensation should be reviewed and adjusted to the principal heavy duties. The amount of compensation should be added.